SURVEI PEMANFAATAN MEDIA PEMBELAJARAN PADA MATA PELAJARAN PENJASORKES SD NEGERI SE-KECAMATAN LASEM KABUPATEN REMBANG TAHUN 2013 (Department of Physical Education, Sport, Health and Recreation, 2014)
Formulation of the problem in the study of How utilization of media State Primary School learning physical education Se-Sub Lasem Rembang 2013?. The purpose of this reseach is to know the description of media utilization in learning on subjects physical education State Primary School se-Sub Lasem Rembang. Data collection method using interviews, questionnaires and documentation. As for the data analysis techniques used are descriptive analysis techniques. The results showed that the utilization of learning media State Primary School physical education se-lasem Rembang District are as follows: the average Football 72,24% is pretty good. Volleyball's average is 58,39% is pretty good. Kasti average is 88,26% Â either. Formula run average 36.6% Â less well. Skip media is the frog 58,09% is quite good. Throwing turbo average is 61.5% is pretty good. The average floor is 37,97% less well. SKJ/gymnastic SSB average is 92,66% Â either. Research conclusions that utilization of instructional media on subjects State Primary School physical education se-Sub Lasem Rembang 2013 quite well.